2014
DOI: 10.1038/ncomms5904
|View full text |Cite
|
Sign up to set email alerts
|

An endocytosis pathway initiated through neuropilin-1 and regulated by nutrient availability

Abstract: Neuropilins (NRPs) are trans-membrane receptors involved in axon guidance and vascular development. Many growth factors and other signaling molecules bind to NRPs through a C-terminal, basic sequence motif (C-end Rule or CendR motif). Peptides with this motif (CendR peptides) are taken up into cells by endocytosis. Tumor-homing CendR peptides penetrate through tumor tissue and have shown utility in enhancing drug delivery into tumors. Here we show, using RNAi screening and subsequent validation studies, that N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
225
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 171 publications
(241 citation statements)
references
References 62 publications
15
225
1
Order By: Relevance
“…It has been demonstrated that binding of the C-terminal end of iRGD to NRP-1 can initiate a bulk transcytosis pathway that involves a novel vesicular transport mechanism (17,19,21). To the best of our knowledge, this transcytosis pathway has never been directly visualized during the transport of a therapeutic nanocarrier to the site of a tumor.…”
Section: Synthesis and Characterization Of Silicasomes For Drug Loadimentioning
confidence: 97%
See 4 more Smart Citations
“…It has been demonstrated that binding of the C-terminal end of iRGD to NRP-1 can initiate a bulk transcytosis pathway that involves a novel vesicular transport mechanism (17,19,21). To the best of our knowledge, this transcytosis pathway has never been directly visualized during the transport of a therapeutic nanocarrier to the site of a tumor.…”
Section: Synthesis and Characterization Of Silicasomes For Drug Loadimentioning
confidence: 97%
“…Binding of the cyclic peptide to the integrins is followed by cleavage and release of the C-terminal end of cleaved iRGD, which mediates the interaction with NRP-1 (this is also known as C-end rule). NRP-1 binding leads to the triggering of a system of vesicles that can assist drug and nanoparticle transport (17,19,21). A schematic demonstrating the mechanism by which iRGD initiates nanoparticle transcytosis is shown in Supplemental Figure 5 (19).…”
Section: Synthesis and Characterization Of Silicasomes For Drug Loadimentioning
confidence: 99%
See 3 more Smart Citations